Analisis Keefektifan Kolam Ikan Lele sebagai Pembersih Kandang Ayam Pak Gatot Blitar - Dicko Syah Purnama Putra; Abdur Rahman (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This research examines the innovative and sustainable management of waste from layer chicken farms carried out in Kendalrejo Village, Srengat District, Blitar Regency. The aim is to provide effective solutions to address the environmental impact of poultry farming activities. The method used was field research with purposive sampling technique, collecting primary and secondary data through observation and interviews, as well as qualitative descriptive analysis. The results showed that the creation of catfish ponds under the chicken coops is an environmentally friendly and economically profitable solution. Chicken manure is utilized as feed for catfish, while collaboration with fishing pond entrepreneurs opens up new business opportunities. This initiative was supported by the local community and the Regional Management Agency, accelerating the recovery of environmental conditions, and strengthening social relations between the community and farm managers. This research contributes to increasing literacy and inspiration for farm owners by providing information on creating catfish ponds as an effective and sustainable waste management solution.